Bendera Merah Putih Dalam Prespektif Bela Negara - Tri Bowo Hersandy Febrianto; Isti Puspitasari; Yohana Sekar Pawening; Irwan Triadi (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2023)
The red and white flag is one of the national identities that symbolises the sovereignty of the Indonesian state. This research aims to explain the resistance raised by the community. The normative juridical approach method is an approach based on primary legal materials by examining theories, concepts, legal principles and laws and regulations. The results showed that state symbols, such as the red and white flag, have a deep meaning in Indonesia's national identity. Actions that denigrate the dignity of the state and its symbols can have a negative impact on the unity and pride of the community.